2014
DOI: 10.5902/217976929931
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos e aplicabilidade das teorias de enfermagem pelos acadêmicos

Abstract: RESUMO: Objetivo: avaliar o conhecimento e a aplicabilidade das teorias de enfermagem pelos acadêmicos de uma faculdade privada, Teresina, Piauí, Brasil. Método: estudo quantitativo com 38 acadêmicos, cuja coleta de dados foi realizada por meio de questionário e analisado no programa Statistical Package for Social Science. Resultados: os acadêmicos compreendem as implicações das teorias de enfermagem para a profissão, 89,4% aplicaram alguma destas na graduação, 84,22% dos acadêmicos conhecem as teorias, já que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
3
5
0
3
Order By: Relevance
“…Nonetheless, the results are considered valid, as they reflect similar conditions verified in larger surveys (3,6,(12)(13) . The limited exposure of undergraduate students to nursing theories in nursing programs may limit their knowledge of the subject, hindering its incorporation into their learning, hence interfering in the development of their competencies (9,12) . Therefore, knowing the theories during training contributes to minimize a deficit in the theoretical understanding of nurses and allows to develop a coordinated thought in their actions, assisting in the professional practice (1) .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Nonetheless, the results are considered valid, as they reflect similar conditions verified in larger surveys (3,6,(12)(13) . The limited exposure of undergraduate students to nursing theories in nursing programs may limit their knowledge of the subject, hindering its incorporation into their learning, hence interfering in the development of their competencies (9,12) . Therefore, knowing the theories during training contributes to minimize a deficit in the theoretical understanding of nurses and allows to develop a coordinated thought in their actions, assisting in the professional practice (1) .…”
Section: Discussionsupporting
confidence: 82%
“…The observation that nursing students' knowledge of theories is vague has also been evidenced in previous studies (9,12,16) , thus demonstrating a partial incorporation or absence of the use of conceptual theories or models in their professional actions. Moreover, students showed that, due to the weakening of approaches on theories in the curricular bases of the courses, professors face challenges in sharing with the students values and beliefs pertinent to the profession, risking that what constitutes the science of nursing might be lost and that its unique contributions to the profession are overshadowed (17) .…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations